2015
DOI: 10.1016/j.jinorgbio.2015.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Novel ruthenium(II) cyclopentadienyl thiosemicarbazone compounds with antiproliferative activity on pathogenic trypanosomatid parasites

Abstract: Searching for new prospective antitrypanosomal agents, three novel Ru(II)-cyclopentadienyl compounds, [Ru(η(5)-C5H5)(PPh3)L], with HL=bioactive 5-nitrofuryl containing thiosemicarbazones were synthesized and characterized in the solid state and in solution. The compounds were evaluated in vitro on the blood circulating trypomastigote form of Trypanosoma cruzi (Dm28c strain), the infective form of Trypanosoma brucei brucei (strain 427) and on J774 murine macrophages and human-derived EA.hy926 endothelial cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 67 publications
2
26
0
Order By: Relevance
“…Tumor volumes (mm 3 ) were calculated as LW 2 /2, where L represents the major axis of the tumor, while W represents the minor axis. 57 Isolation of Tumor-Infiltrating Leukocytes. Primary 4T1 tumors were minced and placed in 5 mL of DMEM containing 1 mg/mL of collagenase I, 1 mM ethylenediaminetetraacetic acid (EDTA), and 2% FBS (all from Sigma-Aldrich) for enzymatic digestion.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor volumes (mm 3 ) were calculated as LW 2 /2, where L represents the major axis of the tumor, while W represents the minor axis. 57 Isolation of Tumor-Infiltrating Leukocytes. Primary 4T1 tumors were minced and placed in 5 mL of DMEM containing 1 mg/mL of collagenase I, 1 mM ethylenediaminetetraacetic acid (EDTA), and 2% FBS (all from Sigma-Aldrich) for enzymatic digestion.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Then, cells were pelleted by centrifuging 10 min at 450g, at 4 °C. 57 Isolation of Splenocytes. The isolation of splenocytes was conducted as previously described.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Previously published in vitro studies have revealed that trithiolato-bridged dinuclear ruthenium(II)–arene complexes were effective against T. gondii [ 14 , 15 , 16 , 17 ], Neospora caninum [ 17 , 18 ], and T. brucei [ 19 ]. To improve the effectivity of these ruthenium complexes, their organic substituents have attracted special attention [ 20 ]. Since many parasites lack de novo synthesis pathways of essential metabolites and have therefore become auxotrophic [ 21 ], it is tempting to conjugate Ru(II) complexes with such metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Thiosemicarbazones derivatives have been exhibited a wide spectrum biological activity, such as antibacterial ( Viñuelas-Zahínos et al, 2011 ), antiprotozoa ( Chellan et al, 2010 ; Britta et al, 2012 , 2014 ; Fernández et al, 2015 ); and antitumor ( Ferraz et al, 2011 ). Triapine ® , the most famous thiosemicarbazone, have been studied in clinical trials for treat different diseases using distinct strategies, including the combination with another drug, according to U.S. National Institutes of Health 1 .…”
Section: Introductionmentioning
confidence: 99%